Coexistence of generalized synchronization and inverse generalized synchronization between chaotic and hyperchaotic systems - Gasri, Ahlem; Ouannas, Adel; Ojo, Kayode S. S.; Pham, Viet-Thanh (Nonlinear Analysis: Modelling and Control, 2018)
In this paper, we present new schemes to synchronize different dimensional chaotic and hyperchaotic systems. Based on coexistence of generalized synchronization (GS) and inverse generalized synchronization (IGS), a new type of hybrid chaos synchronization is constructed. Using Lyapunov stability theory and stability theory of linear continuous-time systems, some sufficient conditions are derived to prove the coexistence of generalized synchronization and inverse generalized synchronization between 3D master chaotic system and 4D slave hyperchaotic system. Finally, two numerical examples are illustrated with the aim to show the effectiveness of the approaches developed herein.